Apua Mater: un progetto per il Parco delle Alpi Apuane nella Valle di Arni - Cresci, Edoardo (Scienze del Territorio, 2018)
For the area of Tre Fiumi (near Stazzema in Lucca district) the 2014 Apuan Alps Park Plan schedules the implementation of an Integrated Local Project aimed at defining an consistent series of actions for territorial enhancement, in particular suggesting the conversion and redevelopment of the area through a restoration of disused plots and buildings due to the cessation of marble mining operations. Laying in a very evocative landscape, Tre Fiumi holds a strategic position in the Park: isolated in the heart of these mountains, it represents at the same time a crossroad of Versilia, Massa and Garfagnana. A graduation thesis in Architectural design at the University of Florence chose to follow these planning guide lines trying to become an opportunity of reflection, hopefully a fertile one, on a certain way to do with territories. The aim of the project is the rebirth of the site as the new Centre of the Apuan Alps Park, first step of a series of possible regeneration and new use projects for a number of close areas with great potential but currently degraded.